Herbal Compounds as an Antidote Against Snake Bite - Dagar P.; Mishra A. (My University, 2025)
Snakebites have been declared a neglected health problem that is considered a national disease by the WHO (world health organisation). Asian countries like India have high snakebite death rates due to short antidotes and poorly equipped doctors. In today's scenario, local resources like herbs need to be used to prepare cheap antidotes and are often available to victims. Snake bites should be viewed as an emergency problem and require additional national guidelines, doctor training, expertise, and human concentration for effective and timely treatment-measures to be taken to ensure the availability and mass production of antidotes. Currently available, antidotes have problems with storage, manufacture, and aspects of the results. Attention should be paid to the natural compound Gedunin with antitoxic effects. To determine Gedunin's therapeutic efficacy, well-designed clinical research is required. This article emphasizes and proves the therapeutic effectiveness of the herbal plant active ingredient Gedunin against snakebites. © 2022 Bentham Science Publishers.